Combustors with Low Emission Levels for Aero Gas Turbine Engines - Guellouh, Noureddine; Szamosi, Zoltán; Siménfalvi, Zoltán (International Journal of Engineering and Management Sciences, 2019)
The aircrafts are responsible for emitting several types of pollutants, especially the pollutants in the form of NOX, CO2, CO, UHC, SOX and Particulate Matter PM (smoke/soot). The impact of aviation emissions on the global is well known, where these emissions modify the chemical and microphysical properties of the atmosphere resulting in changes of earth’s climate system, which can ultimate in critical changes in our planet fragile ecosystem, also the pollutants produced by aircraft engines cause many health problems. This is why the International Civil Aviation Organisation (ICAO) is seriously seeking to control the emission levels by issuing new standards during the successive meetings of the Committee on Aviation Environmental Protection CAEP (CAEP/01 in 1986, CAEP/2, CAEP/4, CAEP/6, CAEP/8, etc). The new regulations include more stringent standards aimed to reduce emission levels, this led to increased interest in low emission technologies. In this paper, a comprehensive review of low emissions combustion technologies for modern aero gas turbines is represented. The current low emission technologies include the high Technologies Readiness Level (TRL) including RQL, TAPS, DAC and LDI. Also, there are advanced technologies at lower TRL including LPP, ASC and VGC.